Going Down Textual Lane: Ibadan in Text and Thoughts: A Review of Under the Brown Rusted Roofs by Abimbola Adunni Adelakun. Published by Kraftgriots, Ibadan, 2008, 252pp.1 - Kole Odutola (Yoruba Studies Review)
As a child born and battered (not buttered) in Lagos, my thoughts about Ibadan people are three-fold. I think of a different accent when they speak English. When you read Niyi Osundare’s article you will moderate that notion. The other stereotype that comes to the mind of this Lagos boy is that Ibadan houses do not have street addresses but you can describe where you are going or looking for by Agboole Oloolu or Agboole Alabẹni (as in Bimbo Adelakun’s Novel). The third stereotype is that people of Ibadan eat a lot of ẹ̀kọ and ọọ̀ ̀lẹ̀ (as in mó̩inmó ́ i̩ ́n-beans pudding in English). I cannot really trace where I got that last one. It will be great to read what people of Ibadan think about Lagos city, i ̀lú iná ń jó ogiri o ̀ ̀ sá - The city where fire burns be the walls remain. The place we sing its praises as aromi ́ ṣá lẹ̀gbẹ lẹ̀gbẹ -The city where water flows in abundance. Let me tell you my story of Ibadan through the eyes of writers and thinkers.